Soil Surface Roughness in Temperate Forest During SMAPVEX19-22 - Victoria A. Walker; Michael H. Cosh; William A. White; Andreas Colliander; Victoria R. Kelly; Paul Siqueira (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Data were collected across multiple forested domains during the Soil Moisture Active Passive Validation Experiment 2019–2022 to improve understanding of soil moisture retrievals under dense vegetation. Soil surface roughness was one of many soil and vegetation parameters sampled during intensive operations periods during the spring and summer of 2022 because of its importance to retrieval accuracy (rougher soils have a higher emissivity and reduced sensitivity to soil moisture compared to smooth soils with otherwise identical characteristics). A total of 410 valid pinboard transects were collected across 24 sites between the two temperate forest domains located in the northeastern United States. Two experimental methods (handheld lidar and ultrasonic robot) were additionally tested at select sites. After removal of topographic slope, the forest floor was found to be relatively smooth with average rms heights of $9+-1 \,{mm}$ in the central Massachusetts domain and $6+-1 \,{mm}$ in the Millbrook, New York domain. These correspond to estimates of the model roughness parameter, $h$ , of 0.31 and 0.16, respectively, which is within the range of accepted lookup table values but smoother than suggested by recent studies retrieving $h$ over forests.